2011
DOI: 10.1148/radiol.11110217
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cathartic Bowel Preparation for CT Colonography: Prospective Comparison of 2-L Polyethylene Glycol and Magnesium Citrate

Abstract: Purpose:To prospectively compare adequacy of colonic cleansing, adequacy of solid stool and fl uid tagging, and patient acceptance by using reduced-volume, 2-L polyethylene glycol (PEG) versus magnesium citrate bowel preparations for CT colonography. Materials and Methods:This study was approved by the institutional Committee on Human Research and was compliant with HIPAA; all patients provided written consent. In this randomized, investigatorblinded study, 50 patients underwent oral preparation with either a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…On the other hand, less residual fluid is generally preferable for CTC data interpretation [ 15 , 16 ] since it results in shorter interpretation times [ 16 ]. Furthermore, in accordance with previous studies [ 10 , 17 ] we found that the left colon was significantly better prepared than the right colon independent of the dietregimens.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, less residual fluid is generally preferable for CTC data interpretation [ 15 , 16 ] since it results in shorter interpretation times [ 16 ]. Furthermore, in accordance with previous studies [ 10 , 17 ] we found that the left colon was significantly better prepared than the right colon independent of the dietregimens.…”
Section: Discussionsupporting
confidence: 93%
“…However, those attempts provided primarily linear diameter assessment in defined colonic segments and not a true volumetric analysis of the entire colon. As for manual semi-quantitative subjective studies assessing residual fluid (8, 14, 15, 19, 28), the percentage of colonic cross-sectional surface area covered by fluid was used, a value that is highly dependent on luminal distension. The present automatically calculated volumetric data are objective, more robust, less error prone, and more sensitive to change compared with random samples and/or linear measures.…”
Section: Discussionmentioning
confidence: 99%
“…Lower dose cleansing regimens resulted in improved patient acceptance rates. In another study half volume polyethylene glycol (two liters) was compared to magnesium citrate in patients undergoing CTC15. Adequate cleansing with better tagging and shorter interpretation times were found in the patients who received the reduced volume PEG.…”
Section: Useful Technical Tips For Ctc Performancementioning
confidence: 99%